2018
DOI: 10.15171/hpp.2018.23
|View full text |Cite
|
Sign up to set email alerts
|

Experimental effects of brief, single bouts of walking and meditation on mood profile in young adults

Abstract: Background: To examine the effects of an acute bout of aerobic exercise and meditation on mood state among young adults. Methods: Participants (N= 66, mean age = 21.3 years) were randomly assigned to walk,meditate, or sit (control) for 10 minutes. Participants’ mood state was monitored before and after the intervention using the Profile of Mood States (POMS) questionnaire. Results: Significant group x time interaction effects were observed for the POMS composite scores (P=0.05). When evaluating three POMS su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…However, participation in active leisure is one of the most important components of healthy behavior and research has shown that physical activity improves overall psychological well-being (Lawlor and Hopker, 2001; Penedo and Dahn, 2005). Exercise is considered effective for people with mild to moderate depression, for patients who prefer non-pharmacological treatments (Kok and ReynoldsIII, 2017), and for those who prefer non-intense physical activity such as walking, which has been linked to an improved mood state (Edwards and Loprinzi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, participation in active leisure is one of the most important components of healthy behavior and research has shown that physical activity improves overall psychological well-being (Lawlor and Hopker, 2001; Penedo and Dahn, 2005). Exercise is considered effective for people with mild to moderate depression, for patients who prefer non-pharmacological treatments (Kok and ReynoldsIII, 2017), and for those who prefer non-intense physical activity such as walking, which has been linked to an improved mood state (Edwards and Loprinzi, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Regular participation in physical activity has many health benefits, including a reduced risk of diabetes, cardiovascular disease and premature mortality, 1-6 as well as enhancing psychological health. 7,8 As such, from a health promotion perspective, promotion of physical activity is of critical importance for living a healthy lifestyle. In addition to the cardiometabolic benefits of physical activity, both acute and chronic physical activity participation demonstrate neurocognitive benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Mood states, as measured by scales such as the POMS, have been shown to be enhanced using a variety of different manipulations, including meditation [ 58 , 59 ], sitting isometric yoga [ 60 ], massage therapy [ 61 ], exposure to nature [ 62 ] and physical activities [ 63 ]. Here, we attribute the observed enhancements in the scores of Vigor-Activity to participation in the study-abroad program.…”
Section: Discussionmentioning
confidence: 99%